Serotonin transporter polymorphism modulates neural correlates of real-life joint action. An investigation with functional near-infrared spectroscopy (fNIRS). (30th April 2015) - Herrmann, M.J.; Bogon, J.; Quester, S.; Cordes, A.; Stenneken, P.; Reif, A.; Ehlis, A.-C.
Highlights: We tested a hypothesis that the functional polymorphism ( 5-HTT LPR) influences hypervigilant behavior. Using NIRS it was possible to measure brain activity during real-life joint action. We confirmed that subjects with the short variant of 5-HTT LPR show increased parietal brain activity. Brain activity is negatively correlated with subjective data in Asperger Questionnaire. Abstract: A functional polymorphism ( 5-HTT LPR) within the serotonin transporter gene ( SERT ) has been associated with personality dimensions such as neuroticism, with emotional reactivity to negative events, and with an increased risk of affective disorders. More specifically, the short (S) allele of 5-HTT LPR has been linked to increased amygdala activity and has been identified as a risk allele for depressive disorders. Recently, Homberg and Lesch (2011) urged for a conceptual change in the current deficit-oriented connotation of the 5-HTT LPR S-allele and argued that the S-allele could be considered adaptive in certain contexts. They postulated that S-allele carriers show hypervigilant behavior in social situations and should thus show increased social conformity. Therefore, we tested whether 5-HTT LPR modulates the neural correlates of real-life social joint action through functional near-infrared spectroscopy (fNIRS). Thirty participants, homozygote for 5-HTT LPR, were measured and analyzed while they were involved in a previously published joint-action paradigm, which reliably leads to an activation of the left parietal cortex. We found that homozygote S-allele carriers showed increased inferior parietal lobe activation, compared to the LL-allele carriers for the contrast "joint action greater solo action". Therefore, our results provide evidence for beneficial effects of the S-allele on the neural correlates of social interactions.